Hungarian Monitoring, 13 October 1989 . [Magyar rádiófigyelő], 1989. október 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: reformist economist Shmelev predicts collapse of Soviet economy; religious service held for the first time in the Kremlin in 70 years - Still no drop in numbers of East German refugees leaving GDR via Hungary - French CP Central Committee in session Domestic Affairs: - Horn and Kohl discuss Eastern European reforms - Draft bill on president of the republic - Alliance of Young Democrats (Fidesz) 2nd congress - Draft Cardinal laws - Patriotic Popular Front congress - Independent Smallholders', Agrarian Workers and Civic Party (FKGP) leaders' meeting - The Standard trial - Catholic church requests re-examination of the Mindszenty trial Economy: - Medgyessy at the World Economic Forum - Japan downgrades Hungarian National Bank shares - Belgian and Canadian financial support - Hungarian car production Külpolitika: - SZU: Smeljov reformközgazdász a szovjet gazdaság összeomlását jósolja ; 70 év után ismét istentiszteletre került sor a Kremlben - Továbbra sem csökken a Magyarországon át az NSZK-ba távozó keletnémet menekültek száma - Ülésezett a francia KP KB-a Belpolitika: - Horn és Kohl a kelet-európai reformokról tanácskozik - Köztársasági elnökről szóló törvényjavaslat - FIDESZ II. kongresszus - Sarkalatos törvénytervezetek - HNF kongresszus - FKGP vezetőségi ülés - Standard - Per - A katolikus egyház a Mindszenty per felülvizsgálatát kéri Gazdaság: - Medgyessy a Világgazdasági Fórumon - Japánban visszaminősítették az MNB Kötvényeit - Belga és kanadai pénzügyi támogatás - A magyar autógyártás ügye